SUFISME ISLAM DALAM BINGKAI GAGASAN PEMIKIRAN BUYA PROF. DR. HAMKA - Arifin, Zainuddin; Santalia, Indo; Thalib, Abdullah; Rasdin, Rasdin (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
Tasawwuf as one of the esoteric teachings in Islam is very urgent which is global today. Historically, the embryo of its existence has not yet stood alone as an Islamic discipline as it is today, but is only an example of axiomatic or badihi moral behavior carried out in the daily life of the Prophet Muhammad, then followed by his companions. When the knowledge and doctrines of the teachings of philosophical Sufism mutated to the era, both pre and modern Islam, their existence received sharp scrutiny and scathing criticism from Islamic scholars plus intellectuals. In particular, in Indonesia, Islamic reformers emerged who took part in the process of puritanism of the extreme teachings of Islamic Sufism. The method used is character study, using an approach through library research, namely; collects references in the form of Buya Hamka's works and the writings of figures who write about Buya Hamka's thoughts that have been published in the midst of Islamic society, especially in Indonesia. Both through print media as well as electronic media and social media, then the author describes and analyzes the argumentation of Buya Hamka's tasawuf thought. The results obtained from writing this article are as follows: Buya Hamka, with his brain intelligence and the sharpness of his analytical knife, concludes that Sufism must be recognized as a very urgent need in human life, in particular, for the life of the Muslim community, because it is through Sufism that we will not experience dryness and spiritual poverty. However, for the sake of enriching our spiritual treasures, we must and must forget and turn our backs on worldly life. That is a very narrow teaching and completely wrong. For this reason, Buya Hamka criticizes the old style of Sufism, then builds and modifies the new model of Sufism, through the ideas that have been poured into several of his monumental works on Sufism.